The Utilization of Bira Tubers (alocasia macrorrhizos) Become Bioplastic with the Addition of Starch Waste of Banana Skins Kepok (musa paradisiaca) - Linda Sekar Utami; M Isnaini (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This study aimed to determine the tensile test size of the bira tuber bioplastic with the addition of kepok banana peel starch. The method used is experimental. A tensile test was carried out with ATSM D882. The research results showed that the four samples' best tensile test added the most bira starch at 40% of 1432 N/m². The color of the resulting plastic is still clear brown because no bleach is added to the starch.